A study of the extent to which lack of teacher motivation affects learner academic performance in rural schools of Shurugwi district - Ngwenya, Siphathisiwe (Midlands State University, 2017)
The teaching and learning process is incomplete when the teachers are not effectively taking part and are demotivated. Most education systems are faced with a motivation crisis which has a far reaching negative implication on learners. The rural schools experience a lot of challenges that affect learner performance through teacher dissatisfaction as the teacher is the center of instruction hence his/her satisfaction guarantee high performance. The study was carried out to find out the extent to which lack of teacher motivation affects learner performance. A descriptive survey was use. Interviews were carried with school heads and questionnaires were administered to teachers. Two schools with the same characteristics as others in the area were chosen as the population and 24 teachers and 2 heads were purposively sampled to take part in the study. The study established that low teacher motivation affected school academic performance and brought about that low job commitment, less learner feedback and ineffective lesson delivery. The study brought to light that teaching and learning environment, remuneration, lack of material resources, educational policies among other factors are major causes of teacher demotivation. The study also brought to light that currently the rural area lack recreation facilities and social services which are a major drawback for teachers as they seek opportunities to move away from rural areas to seek these services in nearby towns which affect learners through teacher absenteeism. Respondents felt that there was need to revise salaries, introduce incentives, involve teachers in decision making and put up consistent policies with the teacher at heart to uplift their motivation levels. The study concluded that there was a very close relationship between learner academic performance and teacher motivation hence low teacher motivation negatively affected learner performance.